ALS562 : Research methodology (Arabic language) / Academy of Language Studies - UiTM, Academy of Language Studies (Universiti Teknologi MARA (UiTM), 2017)
This course aims to equip students with a knowledge of various methods appropriate for research. Students will become familiar with the systematic processes needed to ensure the reliability and validity of quantitative and qualitative research. The course emphasises theoretical and practical issues in research design and methodology. At the end of the course, the students demonstrate their knowledge and skills acquired in a research proposal.